Articles (Academy of Management Journal, 1961)
Presents news briefs about organizations and institutions associated with business management, as of April, 1961. Information on the Southern Case Writers Association; Appointment of J.K. Bailey into the fraternity Σ Iota Ε; Management course at the University of Cambridge, England.